Pengembangan Lembar Kerja Mahasiswa Bernilai Karakter Berbasis Problem Based Learning - Ninik Indawati; Yuli Ifana Sari; Nelya Eka Susanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to develop problem-based learning student worksheets with character values ​​and test their effectiveness in increasing student character values. The research method used is research and development with the stages of developing worksheets, validity and reliability tests, field trials, and data analysis. The research sample was students of the Master of Social Science Education Study Program at PGRI Kanjuruhan University, Malang, consisting of 30 students. The results showed that the development of student worksheets with problem-based learning was effective in increasing student character values. This can be seen from the increase in student character values ​​after using this worksheet, as well as student activity and creativity in the higher learning process. In addition, this worksheet also helps students identify problems and find the right solution. Based on these findings, it can be concluded that the development of problem-based learning student worksheets can be an effective learning alternative to improve student competency in facing future challenges. The use of this worksheet needs to be considered as a learning strategy in higher education